2017
DOI: 10.1371/journal.pone.0178239
|View full text |Cite
|
Sign up to set email alerts
|

Considering reefscape configuration and composition in biophysical models advance seascape genetics

Abstract: Previous seascape genetics studies have emphasized the role of ocean currents and geographic distances to explain the genetic structure of marine species, but the role of benthic habitat has been more rarely considered. Here, we compared the population genetic structure observed in West Pacific giant clam populations against model simulations that accounted habitat composition and configuration, geographical distance, and oceanic currents. Dispersal determined by geographical distance provided a modelled genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 62 publications
(83 reference statements)
1
10
0
Order By: Relevance
“…The availability of suitable habitat patches has been suggested to be important for successful dispersal and gene flow in other marine species (D’Aloia et al, 2015; Selkoe et al, 2010; Van Wynsberge et al, 2017). We found that both geographical distance and the length of gaps in suitable habitat (here: eelgrass beds) had significant, positive effects on genetic difference between sample localities (Table 3; Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…The availability of suitable habitat patches has been suggested to be important for successful dispersal and gene flow in other marine species (D’Aloia et al, 2015; Selkoe et al, 2010; Van Wynsberge et al, 2017). We found that both geographical distance and the length of gaps in suitable habitat (here: eelgrass beds) had significant, positive effects on genetic difference between sample localities (Table 3; Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Within seascapes, specific habitat attributes ("seascape features") can mediate the flow and access of materials among habitats, resulting in varying effects on biological communities. These interactive seascape features can be grouped into broad categories: (1) the spatial arrangement of habitats and (2) the composition of habitat (Olds et al 2015, Staveley et al 2017, Van Wynsberge et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Inherently connected to seascape genomics, we define reefscape genomics as spatially explicit studies focused on a within-reef scale that use reefscape attributes and processes as statistical predictors of genomic variation. This follows a recent call to expand seascape characterization to specifically include the benthic component (Van Wynsberge et al, 2017), but we argue the additional value of doing so at a high spatial resolution. Such fine-scale characterization of the reefscape has recently been made possible due to advances in computer vision, and further facilitated by the increased accessibility of the underwater environment (e.g., through autonomous underwater vehicles, dive propulsion vehicles, and closed-circuit rebreathers).…”
Section: Introductionmentioning
confidence: 79%